Visualising natural attractions within national parks: Preferences of tourists for photographs with different visual characteristics. - Lei Zhu (Public Library of Science (PLoS), 2021)
To explore what types of photographs are more helpful means to interpret natural attractions within national parks, this study focused on the relationship between the photographs with different visual characteristics and their perceived visual appeal. A photograph-based Q method was adopted. Results confirmed the visual quality of a photograph was the most important characteristic that determined its perceived attractiveness; those photographs with a high visual quality could successfully attract tourists' attention. The subject also significantly affected the preferences of observers, suggesting an interest-dependent pattern. Using photographs of birds as examples, the participants who were interested in birds were attracted by the photographs of birds rather than those of other subjects. This study provides a better understanding of the effectiveness of photographs for communication. Findings may help researchers, communicators and national park marketers better understand and select appropriate photographs for interpretation within national parks.